Medical Student’s Perspectives on Educational Environment: A Cross-sectional Study from a South Indian Rural Medical College - N Asha Rani; Aliya Nusrath; M G Shivaramu (Journal of Medical Sciences and Health, 2019)
Background: The World Federation for Medical Education draws special emphasis on learning environment as one of the targets for the evaluation of medical education system. Students satisfaction on education environment strongly influences their approach to learning and the quality of learning outcome. Objectives: The objectives of the study were to assess the student’s perception on educational environment using the Dundee Ready Education Environment Measure (DREEM) questionnaire among 2nd year undergraduate medical students. Materials and Methods: A cross-sectional study was conducted among 2nd year undergraduate medical students. A globally accepted DREEM questionnaire was used as a tool to gather student’s perception toward the educational environment. DREEM questionnaire consists of five components with 50 statements assessed on five-point Likert scale (0–4). After obtaining ethical clearance, questionnaire was distributed among consented participants (n = 130). The completed questionnaires were collated for statistical analysis. Data were expressed as mean and SD, frequency, and percentages. McAleer and Roff practical guidelines were used to analyze and interpret the responses. Results: The response rate was 86.15%. The overall mean DREEM score was 127.4 ± 29 (63.7%). Among the five domains of DREEM, academic self-perception was scored highest (69.9%) and social self-perception was scored least (60.4%). Statements “teachers are knowledgeable” and “I am confident about passing this year” scored ≥3 of 4 points. Conclusion: The overall mean DREEM score was indicative of “a more positive than negative perception.” The more constructive responses were on student’s confidence, teacher’s knowledge, and curricular relevance, encouragement to participate in teaching session, teacher’s preparedness, and on having good friends in the campus. Nevertheless, there is a room for improvement in weaker areas such as student’s boredom and creative teaching.